2013
DOI: 10.1001/jamasurg.2013.1442
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography-Guided Bilateral Rectus Sheath Block vs Local Anesthetic Infiltration After Pediatric Umbilical Hernia Repair

Abstract: clinicaltrials.gov Identifier: NCT01015053.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…1 Transversus abdominis plane block (TAPB) and rectus sheath block (RSB) are the 2 main types of abdominal wall truncal blocks that are suitable for this purpose. [2][3][4][5][6][7] Compared with epidural anesthesia, more local anesthetic is required for truncal abdominal blocks to be effective. To date, however, chronological changes in blood concentrations of local anesthetics have not been compared between TAPB and RSB.…”
mentioning
confidence: 99%
“…1 Transversus abdominis plane block (TAPB) and rectus sheath block (RSB) are the 2 main types of abdominal wall truncal blocks that are suitable for this purpose. [2][3][4][5][6][7] Compared with epidural anesthesia, more local anesthetic is required for truncal abdominal blocks to be effective. To date, however, chronological changes in blood concentrations of local anesthetics have not been compared between TAPB and RSB.…”
mentioning
confidence: 99%
“…Rectus sheath blocks provide analgesia of the periumbilical area by blocking neural transmission of the 9th, 10th, 11th, and 12th intercostal nerves that run between the rectus abdominis muscle and the posterior rectus sheath [7]. RCTs have shown rectus sheath blocks to provide superior post-operative analgesia when compared to local anesthetic infiltration of a surgical wound [9][10][11]. Combined TAP and rectus sheath blocks are an emerging regional anesthetic technique that is safe, effective, and useful adjunct as part of a multi-modal pain management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to placebo or local wound infiltration analgesia, the rectus sheath block results in lower pain scores with opioid-sparing effects in both children and adults receiving umbilical hernia repair [56,57,59]. Study reports have also demonstrated that this block provides effective pain control in surgeries involving midline incisions [60,61].…”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%